Illuminating Meshworks of Pre-Service Teachers’ Curated Co-Living Learning Spaces - Keith, Erin; Clarke, Carolyn; Tucker, Allison (The Canadian Journal of Action Research, 2024)
Learning spaces in higher education are fraught with colonial barriers such as teacher-centered, front facing, stark, feelingless, and unwelcoming classrooms that diminish students’ feelings of well-being. For pre-service teachers, these are also the types of classrooms that they often inherit as they foray into the profession. Three Bachelor of Education (B.Ed) assistant professors investigate how pre-service teachers’ well-being shifted when collectively (re)imagining and (re)envisioning a colonial university classroom space in a faculty building that is over 100 years old. They then share the findings of their a/r/tography, action research inquiry that captured the co-living, metabolic experiences and relational meshworks of both participants (n=11) and researchers documented through reflexive journaling, artistic artifacts, interviews (n=3), and contemplation. The researchers embody decolonizing praxes through intentional interpretation and writing scholarship as they weave their storied inquiry. They conclude with transformative urgencies for how B.Ed programs can recalibrate their physical learning spaces to better support and sustain teachers’ well-being in their future profession.